Exploring agency in entrepreneurship development - A narrative approach - Peura, Kirsi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The thesis builds on a gap in research by examining personal agency among entrepreneurship development professionals, which is currently an under-researched and under-theorized area in the field of entrepreneurship. While the focus on extant research is on professions and a function-based view of entrepreneurship development, it downplays the role of subjectivity and rarely uses individuals as a unit of analysis. To address this issue, this study uses an open interviewing method to explore subjectively perceived maneuver spaces, limitations, and opportunities for agency among entrepreneurship development professionals. The term agency is used in this study to refer to the capacity of individuals to act intentionally and according to plan in a biographical mode. The study is influenced by an epistemology of both constructionism and social constructionism, and an interpretive theoretical perspective. It employs narrative methodology to study agency as enacted and represented in and through language, and is concerned with how meaning is constructed. In the study, narratives are perceived as one form of self-interpretation, and the narrative approach has been used as a tool to explore the agents’ own configurations of concern in entrepreneurship development and how they are factored into sense-making and assuming agentic positions in entrepreneurship development. The research question is, how do participant-narrators in this study understand and make meaning of agency in entrepreneurship development? The research data consists of personal narratives from four local development agents in a post-transitional country, Croatia, and the data was collected from each study participant in two interview sessions, in 2012 and 2014. The study participants present some of the most far-reaching efforts to enhance startups, entrepreneurial behavior, and the competitiveness of SMEs through providing appropriate training and education (university and center for entrepreneurship), facilities and space (technology park), and capital (commercial bank) to nascent and active entrepreneurs. In the narrative presentation and analysis of the research data, the study has separated the “telling” (the process) and the “told” (product), and has positioned the researcher in the process. Data is presented in the form of reconstructed narratives. In the analysis, what has been regarded as agentive action in this talk has been found both in the content and form of narrative sense-making. Tensions and breaches indicated in the narrative telling have acted as an analytical tool to reflect how agency is constructed. The results indicate that in the narrative telling agency is framed by imperatives related to the narrators’ expertise and knowledge, professionalism and procedural mastery, and finally, also moral and intrinsic motives. The findings are that the different elements that come into play to both delineate and, conversely, to provide opportunities for agentic behavior are found in the intersections of the cognitive, behavioral, and conative perspectives. The main implication for the theory and research is that the concept of agency offers a fruitful way to bridge different—new as well as existing, but previously detached—perspectives on entrepreneurship developers, thereby providing potentially better and richer ways to understand entrepreneurship development work. This study proposes that it is not sufficient to perceive and examine agency and agentic outcomes in entrepreneurship development only through the analysis of stereotyped models and action outcomes. Thus, explicit and precise rules for entrepreneurship development practice may be hard to materialize as intended because of the human elements; development work necessarily involve the individual involvement and interpretation. The discussion of the results also advances our understanding around the agency of entrepreneurship developers and the ways it can impact entrepreneurship development in given contexts. Overall, the thesis contributes to topical discussions in entrepreneurship development with novel theoretical, methodological, and empirical results, and contributes to the extant interpretive literature on entrepreneurship development.